American Romanticism, Poe and “The Rationale of Verse” - Saša Simović; Marija Mijušković (American and British Studies Annual, 2016)
Although “The Philosophy of Composition” is usually referred to as Edgar Allan Poe’s best-known critical essay,“The Rationale of  Verse” can certainly be seen as his most elaborate. “Rationale” presents a consideration of the poem as a unit with elements that function together as a unique achievement of a single effect. In this essay Poe developed his “mathematical approach” to a poem in minute detail, emphasizing his proposition that verse is based on time as it is in music, not on accent. This paper will highlight Poe’s most significant ideas on versification and poetry as expressed in “The Rationale of Verse” as well as reveal the basic shortcomings of the essay, a text which can be said to represent the first significant American attempt at laying out the foundations for a modern science of English language verse.